Formação de professores de Matemática e tecnologias digitais: um estudo sobre o Teorema de Tales - Leite, Rubervan da Silva (2017)
This research aims to identify the integration of didactic, specific and technological knowledge that a group of undergraduate students in Mathematics of the State University of Pará possess, related to the theorem of Tales. This is a qualitative research, in which the methodology was based on the application of activities so that the students had to use Geogebra software in the resolution of them. The activities were based on a sequence of progressive complexity, in which students were asked to demonstrate that their conjectures were mathematically valid. In addition, their technological know-how should be refined, so that they develop fluency in relation to the interfaces used. Integrated into these two cognitive fields, it was expected that the didactic knowledge needed to work with the theorem of Tales in teaching situations would emerge. The analyzes were carried out in order to observe the resolutions presented by each subject and to identify the extent to which the answers provided evidenced integration between three types of knowledge, in the molds proposed by TPACK. It was observed that the students presented misunderstandings related to the specific knowledge, in the same extent they indicated that they had doubts regarding the didactic and technological knowledge necessary to achieve the sequence to which they were submitted, which led to the study making recommendations in the sense that differentiated approaches for the mathematics teachers education processes of Mathematics are conceived so that the three aspects of knowledge mentioned here can be contemplated in an integrated way